In Islandia, VERITAS: Characterization of Venus Surface Analogs - Nunes, Daniel C.; Smrekar, Suzanne E.; Hensley, Scott; Adeli, S.; Alemanno, Giulia; Andrews-Hanna, Jeff; Buczkowski, D.L.; Campbell, B.A.; Cascioli, G.; Di Achille, G.; Domac, Akin; Dyar, M; et al. (2024)
At the intersection of the Atlantic mid-ocean ridge and a mantle hotspot, Iceland hosts a variety of volcanic and tectonic features similar in morphology and rock type to those observed on Venus. In July of 2023, the VERITAS science team and collaborators conducted a multipronged field analog campaign to (i) serve as a development and test platform for processing and analysis of Venus and Venus-analog data, and (ii) create a library of surface features to inform interpretation of past and upcoming Venus data.